Presidents in trouble: Presidential approval of Alan García (2005-2011) and Ollanta Humala (2011-2016) - Quiñón, Aarón (2016)
Peru not only is a presidentialist country, but also is a democracy without parties and a state with poor politic system institutionalized. In this context, the president’s leadership is important to explain the dynamic politic of the country. Since the return of democracy in 2001, presidents enter with high levels of approval but end with low levels. Paradoxically, that dynamic develop in a context of growth economic and boom of commodities, debating with main explains of politic behavior focus in economic performance, party affiliation and politic leadership. However, the discussion about relationship with politic system and president’s dynamic in presidential approval was little. From an analysis of the processes and politics dynamics to the governments of Alan García (2006-2011) and Ollanta Humala (2011-2016), this investigation argues that there is a close relationship begin politic system post-Fujimori and highs levels of presidential’s disapprove. In that sense, the high level of presidential’s disapprove will be reflection of a political class delegitimized due to the permanence of an anti-government discourse, breach of electoral promises, absence of a solid party apparatus and a poorly redistributive economic system, these being the characteristics of the post-Fujimori political system. Finally, president’s personality, his management capacity and initiative, and control of politics joints will be crucial to demonstrate fragility of presidential figure. In this way, the dynamic of economic growth has demonstrated the institutional poverty of Peruvian political system demonstrating in the presidential disapproval.